Family Socialization of Adolescents Convicted of Crimes of Varying Severity - Albina A. Nesterova; Leonid M. Levin (Peoples' Friendship University of Russia (RUDN University), 2023)
Features of family functioning and parent-child interaction affect the success of the socialization process, because parental attitudes and habitual ways of behavior are subsequently reproduced by children in further interaction in society. Aspects of family socialization of adolescents who have committed crimes of varying severity have been little studied in Russia. The purpose of the study is to determine the nature of interaction with parents and the features of family socialization of male adolescents convicted of crimes of varying severity. The study involved 280 adolescents, of whom 120 were serving sentences in juvenile correctional facilities, 80 were given and were registered with the penitentiary inspection, 80 were studying in educational institutions in Moscow and had never been held brought before the law for offenses. The average age of the participants was 15.8±0.8 years, all the respondents were male. As main methods the authors used interviews and analysis of personal files as well as a number of psychodiagnostic methods, including: The Scale of Tactics of Behavior in Parent-Child Conflict (adapted by I.A. Furmanova); A Questionnaire on Family Emotional Communications (A.B. Kholmogorova, S.V. Volikova, M.G. Sorokova); Unfinished Sentences Sacks - Sidney Variant (modified by T.A. Zaeko). The results of the study revealed the following reliably significant characteristics of the family socialization of convicted adolescents: living in an incomplete family, dissatisfaction with the financial situation, narcotization and alcoholization of parents, deprivation of parental rights of one of the parents, problems with the law of one of the family members, and fewer children in the family. In the families of adolescents convicted of serious crimes, there was a high level of cruelty and violence against the child on the part of the parents manifested. In the families of probationers, there was a lack of clear rules and methods of discipline, neglect of the child's needs. The families of all the adolescents with unlawful behavior were characterized by a dysfunctional nature of communication (communication on the part of the parents was dominated by criticism, causing anxiety, prohibiting the expression of emotions, fixating on negative experiences, etc.). The information obtained in the study can be used by employees of the psychological and educational services of the penitentiary system.